ANALYSIS OF LOCATION SELECTION FOR ABC CELL UMKM BUSINESS USING THE BREAK EVEN POINT METHOD - Syarifudin , Achmad; Wirawati, Sri Mukti (AGUSPATI Research Institute, 2025)
This research aims to determine optimal business locations, namely Kiosk Ramayana and Kiosk JL Banten, using the main evaluation method: Break-Even Point (BEP). The BEP evaluation measures the time required to reach breakeven, with the results of Kios Ramayana achieving BEP at 0.92 units and Kios Banten at 0.83 units, indicating Kios Banten is faster in this aspect. Further analysis indicates that while Kios Banten has a short-term financial advantage through lower BEP, Kios Ramayana offers the best combination of long-term profitability and other strategic factors. Therefore, Kios Ramayana was chosen as a superior business location. This research concludes that in choosing a business location, it is important to consider not only financial aspects but also strategic and non-financial factors for a more balanced and sustainable decision.